BioMedInsight: Innovative Approaches in Epigenetic Profiling for the Development of Personalized and Targeted Cancer Therapy - Az-Zahran, Muhamad Hisyam; Putri, Annisa Angelita; Fachrya, Athiya (Syntax Literate, 2025)
This study aims to develop an innovative approach to personalized cancer treatment through the analysis of epigenetic profiles using the BioMedInsight platform. The primary issue in current cancer treatment is the lack of personalization, often resulting in limited therapy effectiveness and undesirable side effects. BioMedInsight integrates multi-omic epigenetic data to identify specific epigenetic modification patterns that can be targeted in cancer therapy. The proposed methods include collecting epigenetic data from public sources, normalizing data, differential analysis, multi-omic data integration, biomarker identification, and developing predictive models of therapy response using machine learning. It is expected that this approach will provide guidelines for the development of more personalized and effective cancer therapies, as well as new insights into the underlying epigenetic mechanisms of cancer. Although this study is an idea and has not been implemented in field research, its potential clinical impact is significant. By leveraging publicly available epigenetic data, we can develop more accurate and specific predictive models for individuals, enabling more tailored and effective therapies. Further research is needed to validate these findings in larger populations and implement them in clinical practice. Preliminary conclusions suggest that this approach has great potential to improve clinical outcomes for cancer patients by providing more specific and personalized information about their epigenetic profiles.